Peroxisome Proliferator-Activated Receptor-Î³ Regulates the Expression of Alveolar Macrophage Macrophage Colony- Stimulating Factor - Bonfield, Tracey L.; Thomassen, Mary Jane; Farver, Carol F.; Abraham, Susamma; Koloze, Mary T.; Zhang, Xia; Mosser, David M.; Culver, Daniel A. (East Carolina University, 2008)
Macrophage CSF (M-CSF) regulates monocyte differentiation, activation, and foam cell formation. We have observed that it is elevated in human pulmonary alveolar proteinosis (PAP) and in the GMCSF knockout mouse, a murine model for PAP. A potential regulator of M-CSF, peroxisome proliferator-activated receptor-Î³ (PPARÎ³), is severely deficient in both human PAP and the GM-CSF knockout mouse. To investigate the role of PPARÎ³ in alveolar macrophage homeostasis, we generated myeloidspecific PPARÎ³ knockout mice using the Lys-Cre method to knock out the floxed PPARÎ³ gene. Similar to the GM-CSF-deficient mouse, absence of alveolar macrophage PPARÎ³ resulted in development of lung pathology resembling PAP in 16-wk-old mice, along with excess M-CSF gene expression and secretion. In ex vivo wild-type alveolar macrophages, we observed that M-CSF itself is capable of inducing foam cell formation similar to that seen in PAP. Overexpression of PPARÎ³ prevented LPS-stimulated M-CSF production in RAW 264.7 cells, an effect that was abrogated by a specific PPARÎ³ antagonist, GW9662. Use of proteasome inhibitor, MG-132 or a PPARÎ³ agonist, pioglitazone, prevented LPS-mediated M-CSF induction. Using chromatin immunoprecipitation, we found that PPARÎ³ is capable of regulating M-CSF through transrepression of NF-ÎºB binding at the promoter. Gel-shift assay experiments confirmed that pioglitazone is capable of blocking NF-ÎºB binding. Taken together, these data suggest that M-CSF is an important mediator of alveolar macrophage homeostasis, and that transcriptional control of M-CSF production is regulated by NF-ÎºB and PPARÎ³.
Keywords: Macrophage CSF; Peroxisome; Pulmonary alveolar proteinosis